Major Occupations and Private Insurance of Working Postpartum Women in Poverty in the United States, 2019 - Bojung Seo; Hongmei Nan (Mary Ann Liebert, 2023)
Background: Although working postpartum women in poverty still have unmet medical needs, relevant research is lacking. Thus, we aimed to determine the five most frequent occupations of U.S. postpartum women in poverty and further examine whether the most frequent occupations are associated with poverty/being uninsured by an employer. Methods: This is a cross-sectional study. We included women who had a job and gave birth within the last 12 months from a 2019 American Community Survey Public Use Microdata Sample. To examine the associations between the most frequent occupations and being in poverty/uninsured through an employer/union, we used age- and race-adjusted and multivariable-adjusted logistic regression models. Results: A total of 14.3% of working postpartum women lived in poverty, and their most frequent major occupations were sales and related work, followed by food preparation and serving-related work, office and administrative support work, health care support work, and cleaning and ground maintenance. A total of 51.2% of women in the most frequent major occupations were uninsured through an employer/union. Compared with women in other occupations, women in the most frequent major occupations had fewer working hours and weeks that included paid leave. In particular, cleaners and ground maintenance workers and food preparation and serving-related workers were most likely to be in poverty and uninsured through an employer/union. Conclusions: Compared with other occupations, the most frequent occupations were more likely to be insecure and less likely to provide health insurance. Our U.S.-based study suggested that current policies regarding employee benefits needed to be improved especially for the most frequent major occupations.